ANALISIS RASIO KEUANGAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) PROVINSI JATIM UNTUK MENILAI KINERJA KEUANGAN PEMERINTAH PROVINSI JATIM TAHUN ANGGARAN 2018-2022 - Jundia, Hilda Salma; Sarwono, Aris Eddy (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Analysis of financial statements, namely breaking down the records in the financial statements that are part of the basic information and examining important or related relationships using quantitative and non-quantitative data for the purpose of obtaining financial data that is considered important in decision-making, The purpose of this study is to be able to evaluate the financial performance of the East Java Provincial Government using an analysis of the regional budget reports for 2018–2022. This type of research is descriptive-qualitative with a case study approach. The information processed is a report on the implementation of the East Java Provincial Government's budget for the 2018-2022 fiscal year obtained from an online publication published on the official website https://djpk.kemenkeu.go.id/. This 53.807% is based on the East Java Provincial Government's LRA data processing for the 2018–2022 fiscal year. The analysis used in the analysis of regional economic indicators is financial ratio analysis, which calculates the degree of independence, the degree of fiscal decentralization, the efficiency ratio, the ratio of effectiveness, and the regional financial capability. The analysis used to analyze regional financial capacity is the calculation of the share and growth rate as well as a map of the capacity of the regional economy. Based on the calculations and analysis of regional economic indicators, it can be concluded that the relationship model for the degree of regional autonomy in Manado City is a better criterion. The level of decentralization of financial activities is still ongoing, but the efficiency ratio is very effective. Based on regional financial capabilities, it can be concluded that the economic situation of East Java Province is still not ideal. Based on market share and growth calculations, the position of East Java Province is in the second quadrant, and the profitability of the East Java province's economy is relatively high.